Jacopo Strada and cultural patronage at the imperial court : the antique as innovation - Jansen, Dirk Jacob, 1953- (Rulers & elites : comparative studies in governance,, 2018)
"In Jacopo Strada and Cultural Patronage at the Imperial Court: Antiquity as Innovation, Dirk Jansen provides a survey of life and career of the antiquary, architect, and courtier Jacopo Strada (Mantua 1515-Vienna 1588). His manifold activities -- also as a publisher and as an agent and artistic and scholarly advisor of powerful patrons such as Hans Jakob Fugger, the Duke of Bavaria and the Emperors Ferdinand I and Maximilian II -- are examined in detail, and studied within the context of the cosmopolitan learned and courtly environments in which he moved. These volumes offer a substantial reassessment of Strada's importance as an agent of change, transmitting the ideas and artistic language of the Italian Renaissance to the North"--